Low prevalence of HTLV1/2 infection in a population of immigrants living in southern Italy. - Loredana Alessio; Carmine Minichini; Mario Starace; Laura Occhiello; Mara Caroprese; Giovanni Di Caprio; Caterina Sagnelli; Luciano Gualdieri; Mariantonietta Pisaturo; Lorenzo Onorato; Gaetano Scotto; Margherita Macera; et al. (Public Library of Science (PLoS), 2018)
To assess the prevalence of HTLV-1 and HTLV-2 infections in a cohort of immigrants living in southern Italy.We screened for antibody to HTLV-1/2 infection 1,498 consecutive immigrants born in endemic areas (sub-Saharan Africa or southern-Asia) by a commercial chemiluminescent microparticle immunoassay. If confirmed in a Western blot assay, which differentiates anti-HTLV-1 from anti-HTLV-2, the positive sera were tested for specific HTLV RNA by a home-made PCR. The immigrants investigated were more frequently males (89.05%), young (median age 26 years), with a low level of education (median schooling 6 years), born in sub-Saharan Africa (79.70%). They had been living in Italy for a median period of 5 months. Only one (0.07%) subject was anti-HTLV-1 -positive/HTLV-1 RNA-negative; he was an asymptomatic 27-year-old male from Nigeria with 6 years' schooling who stated unsafe sexual habits and unsafe injection therapy.The data suggest screening for HTLV1 and HTLV-2 infections all blood donors to Italy from endemic countries at least on their first donation; however, a cost-effectiveness study is needed to clarify this topic.